An overview of security ontologies - Hélder Gomes (2012)
This paper presents an overview of ontologies in Information Systems Security. Information Systems Security is a broad and dynamic area that clearly benefits from the formalizations of concepts provided by ontologies. After a very short presentation of ontologies and Semantic Web, several works in Security Ontologies targeting different aspects of security engineering are presented together with another study that compares several publicly available security ontologies.